Effect of the biodegradation rate controlled by pore structures in magnesium phosphate ceramic scaffolds on bone tissue regeneration in vivo. (15th October 2016) - Kim, Ju-Ang; Lim, Jiwon; Naren, Raja; Yun, Hui-suk; Park, Eui Kyun
Graphical abstract: Abstract: Similar to calcium phosphates, magnesium phosphate (MgP) ceramics have been shown to be biocompatible and support favorable conditions for bone cells. Micropores below 25 μm (MgP25), between 25 and 53 μm (MgP53), or no micropores (MgP0) were introduced into MgP scaffolds using different sizes of an NaCl template. The porosities of MgP25 and MgP53 were found to be higher than that of MgP0 because of their micro-sized pores. Both in vitro and in vivo analysis showed that MgP scaffolds with high porosity promoted rapid biodegradation. Implantation of the MgP0, MgP25, and MgP53 scaffolds into rabbit calvarial defects (with 4- and 6-mm diameters) was assessed at two times points (4 and 8 weeks), followed by analysis of bone regeneration. The micro-CT and histologic analyses of the 4-mm defect showed that the MgP25 and MgP53 scaffolds were degraded completely at 4 weeks with simultaneous bone and marrow-like structure regeneration. For the 6-mm defect, a similar pattern of regeneration was observed. These results indicate that the rate of degradation is associated with bone regeneration. The MgP25 and MgP53 scaffold-implanted bone showed a better lamellar structure and enhanced calcification compared to the MgP0 scaffold because of their porosity and degradation rate. Tartrate-resistant acid phosphatase (TRAP) staining indicated that the newly formed bone was undergoing maturation and remodeling. Overall, these data suggest that the pore architecture of MgP ceramic scaffolds greatly influence bone formation and remodeling activities and thus should be considered in the design of new scaffolds for long-term bone tissue regeneration. Statement of Significance: The pore structural conditions of scaffold, including porosity, pore size, pore morphology, and pore interconnectivity affect cell ingrowth, mechanical properties and biodegradabilities, which are key components of scaffold in bone tissue regeneration. In this study, we designed hierarchical pore structure of the magnesium phosphate (MgP) scaffold by combination of the 3D printing process, self-setting reaction and salt-leaching technique, and first studied the effect of pore structures of bioceramic scaffolds on bone tissue regeneration through both in vitro and in vivo studies (rabbit calvarial model). The MgP scaffolds with higher porosity promoted more rapid biodegradation and enhanced new bone formation and remodeling activities at the same time.